Film Breakdown and Nano-Porous Mg(OH)2 Formation from Corrosion of Magnesium Alloys in Salt Solutions. Issue 4 (21st January 2015) - Brady, M. P.; Rother, G.; Anovitz, L. M.; Littrell, K. C.; Unocic, K. A.; Elsentriecy, H. H.; Song, G.-L.; Thomson, J. K.; Gallego, N. C.; Davis, B.
Abstract : Small angle neutron scattering (SANS) and scanning transmission electron microscopy (STEM) were used to study film formation by magnesium alloys AZ31B (Mg-3Al-1Zn base) and ZE10A (Elektron 717, E717: Mg-1Zn + Nd, Zr) in H2 O and D2 O with and without 1 or 5 wt% NaCl. No SANS scattering changes were observed after 24 h D2 O or H2 O exposures compared with as-received (unreacted) alloy, consistent with relatively dense MgO-base film formation. However, exposure to 5 wt% NaCl resulted in accelerated corrosion, with resultant SANS scattering changes detected. The SANS data indicated both particle and rough surface (internal and external) scattering, but with no preferential size features. The films formed in 5 wt% NaCl consisted of a thin, inner MgO-base layer, and a nano-porous and filamentous Mg(OH)2 outer region tens of microns thick. Chlorine was detected extending to the inner MgO-base film region, with segregation of select alloying elements also observed in the inner MgO, but not the outer Mg(OH)2 . Modeling of the SANS data suggested that the outer Mg(OH)2 films had very high surface areas, consistent with loss of film protectiveness. Implications for the NaCl corrosion mechanism, and the potential utility of SANS for Mg corrosion, are discussed.